Mediation role of management commitment on improving fraud prevention in primary healthcare: Empirical evidence from Indonesia - Surna Lastri (Problems and Perspectives in Management, 2022)
Fraud in primary healthcare (PHC) is an important and relevant topic to study because of its impact on the state in terms of financial losses and a decrease in the quality of PHC. This study is also relevant because previous studies that formulate a model and measure fraud prevention comprehensively are still limited. It aims to examine the mediating role of management commitment on the effect of apparatus competence and internal control system on fraud prevention. The sample comprises 78 PHCs and 234 senior managers as respondents in Aceh Province, Indonesia. Data for this study were collected using questionnaires from March to July 2021. Structural equation modeling was used to examine a causal relationship between the variables. The result shows that apparatus competence and internal control system positively affect management commitment and fraud prevention with p-value 0.000 (p > 0.01). Likewise, management commitment has a positive effect on fraud prevention with p-value 0.000 (p > 0.01). The findings show that management commitment mediates the relationship between the internal control system and fraud prevention. At the same time, the apparatus competence does not directly affect fraud prevention. The practical significance of this study is the importance of implementing an effective internal control system and high management commitment as a mediating variable for fraud prevention. AcknowledgmentsThe authors are very thankful to the University of Muhammadiyah Aceh, which has supported this study, and all those who have contributed to this investigation.